The Malaysian youth acceptance level on plastic bag campaign through the social media advertising / Noorita Mohammad ... [et al.] - Mohammad, Noorita; Abdul Ghani, Nur Ainiey Aida; Che Abdul Ghani, Che Ros Alia; Mazlan, Miza Afifah; Mohammad Bakri, Muhammad Adib; Izzul Areef, Mohammad Khairi (Universiti Teknologi MARA, Kedah, 2021)
This research examined the influence of soci al media advertising conducted on young people. The incidence June 2021 Keywords: Social media, No plastic bag campaign , environment, youth Corresponding Author: Noori545@uitm.edu.my of landfill spillover with pl astic bags has increased drastically especially during the pandemic Covid 19 due to the huge usage rate of plastic consumption among consumers. This situation could be prevented if the young consumer has a high awareness of the effect of plastic on the environment. Therefore, this study aims to explore the relationship between environmental awareness and social responsibility of youth response and their acceptance of the ‘No Plastic Bag Day’ campaign through social media. The online survey was designed and distributed targeting youth in Malaysia. The result of the analysis showed that environment awareness indicated a significant relationship to influence the youth on their acceptance to wards ‘No Plastic Bag Day’ campaign, while social responsibility is not significant. Finally, all independent variables contributed 54.4 % to the dependent variable, while the rest were explained by other variables not examined in this r esearch. In this re lation, marketers, the industry, and policymakers decision can use these findings to cater to this group segment in the future.